THE EFFECTS OF NITRIDING TIME-TEMPERATURE AND COMPOSITION OF GAS MIXTURE ON THE MECHANICAL PROPERTIES OF INDEXABLE INSERTS - Akca, Cem; Karaaslan, Ahmet; Ozdemir, Ufuk (TANGER LTD, 2009)
Plasma (ion) nitriding is an extension of conventional nitriding processes. Metallurgically versatile, the process provides excellent dimensional control and retention of surface finish. Plasma nitriding can be conducted at temperatures lower than those conventionally employed. Plasma nitriding also achieves repetitive metallurgical results and complete control of the nitrided layers. This control results in superior fatigue performance, wear resistance, and hard layer ductility. In this study, Bohler TPKN 2204 PDR SBF inserts have been investigated using various nitriding parameters: nitriding time, temperature and the composition of gas mixture. The effects of process parameters were examined in terms of hardness and thickness of the nitrided layer. The results have shown that the maximum hardness (at the edge of the specimen) could be achieved with 700 degrees C, 75% H(2) + 25% N(2) mixture and 2 hours process time combination.
Keywords: nitrid; time temperature; substrate; gas mixture; SURFACE ENGINEERED COATINGS; CUTTING TOOLS; WEAR; Metallurgy & Metallurgical Engineering